Effectiveness of Treatment Through Nervous Electrical Stimulation in Chronic Migraine - Nunes, Antonio Jakeulmo; Faheina, Lucas Ribeiro Fernandes; Santos, Késley Thuanya Fontenele dos; Almeida, Luan Lopes da Silva; Piloni, Bianca dos Anjos; Dantas, Kaline Santos; Filho, João Otávio Medeiros Araújo; Pereira, Diuliane Teixeira; Almeida, Ruanis Anastácio de; Almeida, Allana Lopes da Silva; Santos, Ana Emília Martins dos; Bezerra, Diogo Alves Peres (Headache Medicine, 2023)
Full abstract in PDF.